Peran Satuan Bakti Pekerja Sosial dalam Memberikan Layanan Perlindungan Sosial Kepada Anak yang Terkena Dampak Pandemi Covid-19 di Kota Bandung - Veronica, Talenta; Riasih, Teta; Susilawati, Susilawati (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2021)
Children are a group that is vulnerable to exposure, also experiencing other problems due to the Covid-19 pandemic. Some of the problems of children affected by the corona virus outbreak, such as child poverty, learning, nutrition, and care and security. Social workers, especially satuan bakti pekerja sosial (sakti peksos) from the Ministry of Social Affairs which are placed in Bandung, are expected to provide protection services for children, especially those affected by Covid-19. This study aims to obtain a deeper picture of the roles of advocates, brokers and educators carried out by Sakti Peksos in Bandung. The researcher used a qualitative approach with descriptive methods with a case study design of the four sakti peksos. The results of this study indicate that children also experience the impact of covid-19, especially in meeting basic needs due to Large-Scale Social Restrictions (PSBB), which are then accessed by social workers. Difficulties of children in meeting their needs are advocated to several related parties, in order to keep children's rights fulfilled. Children's problems are also connected to several source systems that can help overcome children's problems. Sakti Pesos also provides education in the form of information needed by children and families.The role of the educator is not performed optimally by the sakti peksos, due to the lack of understanding of the sakti peksos in providing education by providing online psychosocial support. Sakti peksos also does not understand how to convey the information needed by children and families.